Band edge modulated conjugated polymers for oxidation prevention - Mahale, Rajashree Y.; Arulkashmir, Arulraj; Dutta, Kingshuk; Krishnamoorthy, Kothandam (Physical Chemistry Chemical Physics, 2012)
The impact of electron transfer (ET) from a series of band edge modulated polymers to atmospheric oxygen is examined in connection with substrate oxidation prevention. Polymers with the highest occupied molecular orbital (HOMO) energy level below and above the oxygen energy level were tested and the former showed better efficiency. Furthermore, the oxidation prevention efficiency of a polymer with lower HOMO increased by two orders of magnitude, when the pores on the film were filled with spherical molecules, [6,6]-phenyl-C61-butyric acid methyl ester. We found that the polymer surface hydrophobicity has little or no influence on oxidation prevention. It is interesting to note that a polymer with a hole mobility of 8 x 10(-10) cm(2) V-1 s(-1) showed a two-fold increase in oxidation prevention efficiency compared to a polymer with a hole mobility of 6 x 10(-5) cm(2) V-1 s(-1). Over all, from the concerted approach, we conclude that a polymer devoid of pores with the HOMO energy level below oxygen and low charge carrier mobility is a suitable candidate for prevention of substrate oxidation/corrosion.

Reversible assembly and disassembly of micelles by a polymer that switches betweenhydrophilic and hydrophobic wettings - Dutta, Kingshuk; Mahale, Rajashree Y.; Arulkashmir, Arulraj; Krishnamoorthy, Kothandam (Langmuir, 2012)
Supramolecular complexes involving nanoscopic amphiphilic assemblies (AAs) and polyelectrolytes have been used to prepare a variety of materials, wherein the dynamic AAs retain the structural features, but the polyelectrolytes undergo conformational changes. Here we show that a charge bearing rigid conjugated polymer can alter the structural features and disassemble AAs. We also demonstrate reversible assembly and disassembly of AAs by controlling the number of charges on the rigid polymer. During the disassembly, the guest molecules sequestered in the AAs are released. The rate of release has been modulated by changing the morphology of the charge bearing polymer. Concomitant to the AAs disassembly, the polymer surface becomes hydrophobic due to the binding of the amphiphiles on the charges of the polymer backbone. By controlling the charges on the polymer, the surface wettability was varied gradually from hydrophilic to hydrophobic.

Supramolecular interaction facilitated small molecule films for organic field effect transistors - Arulkashmir, Arulraj; Mahale, Rajashree Y.; Dharmapurikar, Satej S.; Jangid, Manoj K.; Krishnamoorthy, Kothandam (Polymer Chemistry, 2012)
Metalloporphyrins and metal free porphyrins have been explored as active materials in field effect transistors. Amorphous forms of these porphyrins are preferred over their crystalline analogue due to the ease of solution processability. To achieve solution processability, a metalloporphyrin was anchored on a vinyl polymer by taking advantage of the supramolecular interaction between the metal and the pyridine moiety of the polymer. Non covalent bonding was preferred because it provides an opportunity to better manipulate the polymer's properties compared to its covalent bonding analogue. The binding between the porphyrin and the polymer was optimised in solution and the supramolecular complex was spun on various substrates to form thin films. The porphyrin was found to be uniformly distributed throughout the polymer films contrary to the existing approaches, wherein small molecule phase segregates in the polymer film. Field effect transistors were fabricated using the porphyrin-polymer complex and the device parameters were measured at atmospheric condition. The devices annealed at 80 degrees C showed hole carrier mobility of 2.0 x 10(-4) cm(2) V-1 s(-1) with charge trapping at the dielectric semiconductor interface. Furthermore, the high carrier mobility observed at low temperature annealing makes this supramolecular complex an attractive candidate to explore in flexible substrates.

Cleavable and removable polymer thermosets for organic field effect transistor packaging - Arulkashmir, Arulraj; Bhosale, Manik E.; Krishnamoorthy, Kothandam (RSC Advances, 2013)
Recent years have witnessed tremendous progress in the design and synthesis of electroactive materials for the fabrication of organic electronic devices. However, very little research effort has been devoted to developing organic packaging materials, which are crucial for the efficient functioning of the devices. Polymer thermosets (PTs) are extensively used for the packaging of microelectronic and optoelectronic devices. Although PTs are effective in providing mechanical stability and environmental protection to devices, the removal of PTs without destroying the underlying surface is cumbersome. Facile removal of PTs is essential to reuse the expensive substrates. Herein, we report the preparation of a thermoset using an aliphatic disulfide containing cross-linker, cystamine. By varying the cross-linker concentration, the mechanical property of the thermoset was varied from ductile to brittle. The ductile thermoset was coated on metal, semiconductor and flexible substrates. The thermosets were then cleaved using a biomolecule in neutral pH. We have demonstrated that the cleavage and removal of thermosets don't affect the surface properties of the underlying substrates. Furthermore, the thermosets were coated on top of organic field effect transistors to provide environmental protection. The thermoset coated devices showed a charge carrier mobility of 5.3 x 10(-3) cm(2) V-1 s(-1). Then, the thermoset was cleaved and removed, and the substrate was reused for the fabrication of organic field effect transistors with unchanged device efficiencies.

Enhanced hole carrier transport due to increased intermolecular contacts in small molecule based field effect transistors - Dharmapurikar, Satej S.; Arulkashmir, Arulraj; Das, Chayanika; Muddellu, Pooja; Krishnamoorthy, Kothandam (ACS Applied Materials & Interfaces, 2013)
Small molecules and oligomers can be synthesized with very high purity and precise molecular weights, but they often do not form uniform thin films while processed from solution. Decreased intermolecular contacts between the small molecules are another disadvantage. To increase the intermolecular contacts in small molecules, we have chosen i-indigo, as one of the conjugated molecular units. The electron poor i-indigo has been connected with electron rich triphenylamine to synthesize a donor-acceptor-donor type small molecule. The propeller shaped triphenylamine helps to increase the solubility of the small molecule as well as isotropic charge transport. The intermolecular spacing between the molecules has been found to be low and did not vary as a function of thermal annealing. This implies that the intermolecular contacts between the small molecules are enhanced, and they do not vary as a function of thermal annealing. Organic field effect transistors (OFET) fabricated using a small molecule exhibited a hole carrier mobility (mu) of 0.3 cm(2)/(V s) before thermal annealing. A marginal increase in mu was observed upon thermal annealing at 150 degrees C, which has been attributed to changes in thin film morphology. The morphology of the thin films plays an important role in charge transport in addition to the intermolecular spacing that can be modulated with a judicious choice of the conjugated molecular unit.
Keywords: hole mobility; i-indigo; organic field effect transistor; quadrupole interaction; small molecules; triphenylamine

Chemically doped perylene diimide lamellae based field effect transistor with low operating voltage and high charge carrier mobility - Arulkashmir, Arulraj; Jain, Bhanprakash; John, Jino C.; Roy, Kanak; Krishnamoorthy, Kothandam (Chemical Communications, 2014)
Chemical doping of an electron transporter results in the formation of a radical anion containing semiconductor which showed high electron mobility (13 cm(2) V-1 s(-1)) at low operating voltage (1 V).

pH-Dependent single-step rapid synthesis of cuo and cu2o nanoparticles from the same precursor - Nikam, Arun V.; Arulkashmir, Arulraj; Krishnamoorthy, Kothandam; Kulkarni, Amol A.; Bhagavatula L. V. Prasad (Crystal Growth & Design, 2014)
A single-step protocol to prepare Cu2O and CuO nanocrystalline particles from the same precursor by microwave irradiation has been developed using the pH of the solution as the only variable parameter. The utility of different bivalent Cu-precursors for synthesis of CuO and Cu2O nanoparticles was also investigated. The morphology, phase purity, and optical properties of these nanoparticles were analyzed using TEM, SEM, XRD, and optical spectroscopy. The band edges were determined using cyclic voltammetry. Field effect transistors based on CuO nanoparticles showed a hole mobility of 3.5 x 10(-2) cm(2) V-1 s(-1), making them a suitable candidate for energy-related applications. The effect of hydrazine vapor exposure on the IV-characteristics of CuO nanoparticles was also investigated. This revealed a decrease in source current with respect to time.

Band edge modulated polymer layer to decrease back electron transfer and increase efficiency in sensitized solar cells - Arulkashmir, Arulraj; Sudhakar, Vediappan; Krishnamoorthy, Kothandam (Advanced Energy Materials, 2016)
Recombination of charges residing in the TiO2 and redox electrolyte is one of the factors affecting the efficiency of dye sensitized solar cells (DSSCs). To circumvent this recombination, inorganic oxide barrier layers and organic silanes have been coated on TiO2/dyes. Due to the insulating nature of these layers, the efficiency increase is not very impressive. Conducting polymers with different band edges are used to suppress the charge recombination. Amongst the four polymers that are used as barrier layers, a polymer with a highest occupied molecular orbital energy at -5.8 eV and lowest unoccupied molecular orbital at -3.1 eV is found to increase the electron life time at TiO2 and decrease the charge recombination. The electron life time is found to be 88 ms. In addition to the long electron life time, the recombination resistance of this polymer is also high (91 Omega). This resistance is 18% higher than that measured for DSSCs without polymer barrier layer. These factors impact the efficiency of DSSCs. DSSCs fabricated with this polymer as barrier layer exhibit an efficiency of 9.2%, which is 22% higher than that of DSSCs without polymer barrier layer.

"Click" polymerization: a convenient strategy to prepare designer fullerene materials - Krishnamurthy, Munusamy; Krishnamoorthy, Kothandam; Arulkashmir, Arulraj; Raghavendra, V.; Murali, Adhigan; Jaisankar, Sellamuthu N.; Murugan, P.; Gurusamy-Thangavelu, Senthil A.; Nasar, A. Sultan; Mandal, Asit Baran; Samanta, Debasis (Materials & Design, 2016)
"Click" polymeric assemblies of fullerenes, thiophenes and aryl compounds were prepared for the first time to study their spectroscopic/chemical/electronic characteristics and possible applications in photovoltaic cells. The GPC and NMR spectroscopic data confirmed a moderate to high degree of polymerization while microscopic pictures showed well-defined arrangements of fullerenes. The FTIR studies indicated that the product is free from starting azide materials, whereas thermogravimetric analysis data suggested a good stability. Band gap of the material was determined using UV-Vis spectroscopy, cyclic voltammetric techniques and compared with computational investigation. The fullerene copolymer was fabricated as acceptor material in a bulk heterojunction photovoltaic cell. (C) 2016 Elsevier Ltd. All rights reserved.

Disassembly of micelles to impart donor and acceptor gradation to enhance organic solar cell efficiency - Arulkashmir, Arulraj; Krishnamoorthy, Kothandam (Chemical Communications, 2016)
A transparent, conducting and low surface energy surface was prepared by disassembly of anionic micelles, which altered the orientation of the donor polymer and imparted gradation between the donor and acceptor. This configuration increased the solar cell device efficiency.

Polymer and graphene layer to increase dye regeneration and suppress back electron transfer in dye sensitized solar cells - Sudhakar, Vediappan; Arulkashmir, Arulraj; Krishnamoorthy, Kothandam (Chemical Communications, 2017)
Dye regeneration was improved by using an optimum quantity of graphene, which was dispersed in a polymer that suppresses back electron transfer. Using this approach, DSSCs with an efficiency of 10.4% have been fabricated.

Synthesis of amphiphilic isoindigo co-polymers for organic field effect transistors: A comparative study - Dharmapurikar, Satej S.; Arulkashmir, Arulraj; Mahale, Rajashree Y.; Chini, Mrinmoy Kumar (Journal of the apllied polymer science, 2017)
In this work, the amphiphilic isoindigo (am-iInd) based conjugated polymers namely poly(am-iInd-DT) and poly(am-iInd-TT) and their regular counterpart poly(reg-iInd-DT) and poly(reg-iInd-TT) were synthesized to compare their opto-electronic and charge transport properties. They were used to fabricate organic field effect transistors. Charge transport properties in conjugated polymers depend upon intermolecular interaction which is strongly affected by the nature of side chains. The amphiphilic nature of the conjugated polymers has little impact on the charge transport properties. The charge carrier mobility of amphiphilic conjugated polymers was comparable with the regular polymers except poly(reg-iInd-DT) which can be correlated by X-ray diffraction and thin film morphology. (c) 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2017, 134, 45461.
Keywords: Alkyl; Applications; Conducting polymers; Copolymers; Optical and Photovoltaic applications; conjugated polymers; High-performance; mobility; Packaging; Semicondoctors; Side-chains; Solar-cells; Thin-film Transformer